2014
DOI: 10.1111/jlme.12146
|View full text |Cite
|
Sign up to set email alerts
|

State Experiences Implementing Youth Sports Concussion Laws: Challenges, Successes, and Lessons for Evaluating Impact

Abstract: While provisions of youth sports concussion laws are very similar, little is known as to how they are being implemented, factors that promote or impede implementation, or the level of compliance in each jurisdiction. We aimed to describe state experiences with implementation in order to inform ongoing efforts to reduce the harm of sports-related traumatic brain injury and to guide future evaluations of the laws' impacts and the development of future public health laws. We conducted key-informant interviews in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 15 publications
0
67
0
4
Order By: Relevance
“…26 Several groups have evaluated the implementation and effectiveness of state concussion laws. Lowrey and Morain 27 found more successful implementation in states where policymakers worked with stakeholders (eg, individuals in the state's department of public health) whose involvement in implementation aided in accounting for contextual barriers and facilitators. Two groups 28,29 found that implementation of the laws, including educational provisions for coaches, was associated with increased SRC knowledge among coaches.…”
Section: Policy Levelmentioning
confidence: 99%
“…26 Several groups have evaluated the implementation and effectiveness of state concussion laws. Lowrey and Morain 27 found more successful implementation in states where policymakers worked with stakeholders (eg, individuals in the state's department of public health) whose involvement in implementation aided in accounting for contextual barriers and facilitators. Two groups 28,29 found that implementation of the laws, including educational provisions for coaches, was associated with increased SRC knowledge among coaches.…”
Section: Policy Levelmentioning
confidence: 99%
“…Generally this is designated in 1 of 3 ways: (1) to a “licensed physician” (Alabama, North Dakota, South Carolina, and Texas), (2) to a “health care provider” (Arizona, Colorado, Delaware, Georgia, Kansas, Mississippi, Missouri, New Hampshire, Nevada, Oregon, Tennessee, Utah, Vermont, and Wisconsin), or (3) to a “licensed health care provider trained in the evaluation and management of concussion” (Alaska, Arkansas, California, District of Columbia, Florida, Hawaii, Indiana, Iowa, Louisiana, Maine, Maryland, Massachusetts, Michigan, Minnesota, Montana, Nebraska, New Jersey, New Mexico, Ohio, Oklahoma, South Dakota, Virginia, and Washington). 11 …”
Section: Principles Of Concussion Legislation To Understand On the Simentioning
confidence: 99%
“…12 If a concussion is diagnosed but symptoms resolve, the athlete is not permitted to return to play that day. 7,11 In states with relevant concussion laws, only if the licensed healthcare provider determines by his or her full evaluation that there was no concussion can the athlete return to play on the same day as a suspected concussion. 5 The licensed health care provider should document his or her evaluation, clearance decision, and ongoing observation of the athlete (whether the athlete is cleared or not) throughout the rest of the contest.…”
Section: Principles Of Concussion Legislation To Understand On the Simentioning
confidence: 99%
“…Some of this research focused on evaluating the direct impact of such laws, 12 while other research focused on evaluating the engagement of key stakeholders prior to enactment 13 and the experiences of those charged with implementation at the state level. 14 Most recently, this journal devoted an entire symposium issue to evaluating multiple dimensions of such laws, and pointing to future uncertainties. 15 At the same time, advances in medical research, 16 and even the acknowledgment of sports associations, 17 suggested that, at a minimum, the initial interventions were a good place to start -with opportunity for reform to follow.…”
Section: Stage Three: Researchmentioning
confidence: 99%